Defining IT “Business Value” Under Conditions of Economic Uncertainty - G. Giannopoulos, Athanasios (Journal of Advances in Management Sciences & Information Systems, 2017)
Investment in Information Technology (IT) has typically been justified as playing a crucial role in assisting business and other Organisations in conducting their business in a more efficient and effective way. The implied “value” that results from such investments is known as “IT business value” and its definition and measurement under conditions of economic austerity and uncertainty is the main subject of this paper. The question is why, under such conditions, many Organisations fail to realize the positive impacts expected from IT investment, which by itself is then rather scarce and difficult to attain. To answer this question we concentrate in this paper on the issues of IT business value measurement and more specifically we attempt to answer the research question of how best to define the “business value” of IT and what factors may affect it. The paper first puts forward the main definitions used for both “IT” and “Business value” in the literature. It then goes on to present and critically examine the most prominent of the existing methodologies for measuring “IT Business value” again by resorting to a relevant literature search. Then, we examine the special influencing factors that are at work in times of economic austerity and uncertainty and puts forward a framework for analyzing IT Business value under conditions of economic austerity. This framework is presented in terms of its elements and a description of their main characteristics and measures (metrics). Finally, before the conclusions, a list of the critical success factors for IT investment is presented which is based on a previous published work of the author.